Thermal responses to environmental constraints in two populations of the oviparous lizard Liolaemus bibronii in Patagonia, Argentina - Medina, Susana Marlin (2009)
Ectotherms change their thermoregulation behaviour according to the available temperatures, photoperiod, and radiation present in their local environment. The influences of the abiotic environment not only affect the body temperature but also most life history traits of populations. The thermal biology of one of the southernmost oviparous lizards, Liolaemus bibronii, was studied at high- and low-latitude sites in Patagonia, Argentina, following the methodology of Hertz et al. [1993. Evaluating temperature regulation by field-active ectotherms: the fallacy of the inappropriate question. Am. Nat. 142, 796-818]. Our results show that L. bibronii lives under thermal-environmental constraints, behaves as a moderate thermoregulator, and shows the lowest body temperature (28 °C) for oviparous liolaemids.